Social environmental influences on physical activity of children with Autism Spectrum Disorders - Schenkelberg, Michaela A. (Kansas State University, 2013)
Background: Children with Autism Spectrum Disorders (ASD) may be at greater risk for not meeting physical activity guidelines than neurotypical children (NT). Influences on physical activity (PA) of children with ASD are unclear and marked characteristics of the disorder pose challenges for developing interventions to promote PA. . The purpose of this study was to explore setting (free play versus structured) and group composition influences on ASD and NT young children's physical activity (LMVPA, MVPA) during a summer camp. Methods: Data were collected on 12 boys (5-6 years) attending an inclusive summer camp. During free play and structured activity sessions, research assistants observed the camp’s social environment and children’s PA using a modified version of the Observational System for Recording Physical Activity of Children – Preschool. Results: In a free play setting, children with ASD spent significantly less time in MVPA while with a peer (1.0% of session time), compared to being with a group of peers (12%) or when alone (13%). In free play, NT peers spent significantly more time in LMVPA when solitary (67%) compared to with a peer (38%) or with an adult (40%). In a structured setting, NT peers had greater LMVPA solitary (72%) social environments compared to being in a group with adult (34%). Conclusion: Preliminary evidence suggests that features of the social environment may influence PA levels of children with and without ASD. Depending on the setting, certain social group contexts may be more PA promoting than others.
Keywords: Physical activity; Autism; Children; Preschool; Environment; Behavioral Sciences (0602); Kinesiology (0575); Physical Education (0523)